Recent research and clinical progress of CTLA-4-based immunotherapy for breast cancer - Zhang, Hongsheng; Mi, Jintao; Xin, Qi; Cao, Weiwei; Song, Chunjiao; Zhang, Naidan; Yuan, Chengliang (Frontiers in Oncology, 2023)
Breast cancer is characterized by a high incidence rate and its treatment challenges, particularly in certain subtypes. Consequently, there is an urgent need for the development of novel therapeutic approaches. Immunotherapy utilizing immune checkpoint inhibitors (ICIs) is currently gaining momentum for the treatment of breast cancer. Substantial progress has been made in clinical studies employing cytotoxic T lymphocyte-associated antigen-4 (CTLA-4) inhibitors for breast cancer, but the cure rates are relatively low. To improve the efficacy of CTLA-4-based therapy for breast cancer, further research is imperative to explore more effective immune-based treatment strategies. In addition to monotherapy, CTLA-4 inhibitors are also being investigated in combination with other ICIs or alternative medications. However, it should be noted that immune-based treatments may cause adverse events. This review focuses on the mechanisms of CTLA-4 inhibitor monotherapy or combination therapy in breast cancer. We systematically summarize the latest research and clinical advances in CTLA-4-based immunotherapy for breast cancer, providing new perspectives on the treatment of breast cancer. In addition, this review highlights the immune-related adverse events (irAEs) associated with CTLA-4 inhibitors, providing insights into the development of appropriate clinical tumor immunotherapy regimens and intervention strategies.